2023
DOI: 10.1057/s41599-023-01552-x
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of information technology governance in the relationship between board characteristics and continuity management during the Covid-19 pandemic in an emerging economy

Abstract: The main aim of the current study is to investigate the relationship between governance characteristics, information technology governance, and continuity management during Covid-19 in an emerging economy. The study also examines the moderating role of information technology governance in the relationship between governance characteristics and business continuity management. The quantitative approach is used by utilising a survey questionnaire. A sample of 232 questionnaire surveys has been collected from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 124 publications
0
2
1
Order By: Relevance
“…Similarly, Huang et al [ 70 ] conclude that companies with higher revenues are more likely to have the resources to monitor and report on ESG issues. Our results contradict Al-Gamrh and Al-Dhamari [ 68 ] who state that the level of disclosure varies depending on the company's size and industry. Fontana et al [ 13 ] also argue that the link between firm size and EP demonstrates that if a company pollutes the environment more, it provides more information to stakeholders.…”
Section: Analysis and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, Huang et al [ 70 ] conclude that companies with higher revenues are more likely to have the resources to monitor and report on ESG issues. Our results contradict Al-Gamrh and Al-Dhamari [ 68 ] who state that the level of disclosure varies depending on the company's size and industry. Fontana et al [ 13 ] also argue that the link between firm size and EP demonstrates that if a company pollutes the environment more, it provides more information to stakeholders.…”
Section: Analysis and Discussioncontrasting
confidence: 99%
“…Previous research has examined the influence of firm-specific characteristics on ED and sustainability performance. For instance, several studies have found empirical evidence indicating a positive correlation between firm size and ED and sustainability performance [ 2 , 11 , 13 , 25 , 29 , 67 , 68 ]. Similarly, Qiu et al [ 10 ] indicate that higher levels of social disclosure leads to grater market values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Participants can access and complete the survey online at their convenience. Additionally, the utilization of an online survey is deemed a safe approach, particularly in light of the recommended social distancing measures to mitigate the risk of contracting the novel COVID-19 pandemic (Almaqtari et al , 2023; Nueangnong et al , 2020). The questionnaire survey consisted of 40 items, carefully developed based on a comprehensive review of relevant literature (refer to Appendix).…”
Section: Methodsmentioning
confidence: 99%